Fluconazole prophylaxis against invasive candidiasis in very low and extremely low birth weight preterm neonates: a systematic review and meta-analysis - Mahmoud Robati Anaraki; Masoud Nouri-Vaskeh; Shahram Abdoli Oskoei (The Korean Pediatric Society, 2021)
Background Evidence shows that fluconazole prophylaxis is an effective treatment against invasive fungal infections in preterm neonates, however, the most efficient schedule of fluconazole prophylaxis for the colonization and mortality of invasive candidiasis (IC) is unknown. Purpose This systematic review and meta-analysis aimed to assess the efficiency of different prophylactic fluconazole schedules in controlling IC colonization, infection, and mortality in very low birth weight (VLBW) and extremely low birth weight (ELBW) infants in neonatal intensive care units. Methods We searched the PubMed, Scopus, Embase, and Cochrane databases using the keywords "candida," "invasive candidiasis," "IC," "fluconazole prophylaxis," "preterm infants," "very low birth weight infants," "VLBW," "extremely low birth weight," and "ELBW." Results Mortality was significantly decreased in a meta-analysis of studies using different fluconazole prophylaxis regimens. The meta-analysis also indicated a significant decrease in the incidence of IC-associated mortality in ELBW infants using the same fluconazole prophylaxis schedules. Conclusion Future studies should explore the effectiveness of other different fluconazole prophylaxis schedules on IC colonization, infection, and mortality.